Pelatihan Bentuk Latihan Teknik Dasar Bola basket Pada Pemain Jombang Basketball Club - Ahmad, Nurdian; Ma'arif, Ilmul; Hamid, Faisol; Sulistyo, Yully Wahyu; Nenggar, Aditya Harja (Community Education Engagement Journal, 2023)
The background of this service activity is based on the important need for basic technical skills in basketball games that can support a player's ability to achieve achievement. Basic techniques such as dribbling, passing, shooting are very important assets for every player because as a guide in the ability to play basketball, the form of basic technique training models always encourages a player to be able to hone skills well. However, players will also have experience of movement activities related to the form of training models. methods carried out with lectures and questions and answers, and practice. The form of this activity includes preparation by preparing materials and materials to be delivered, implementation related to providing explanations related to basic basketball techniques and field practice, evaluation related to elements summarising activity events related to the existence of obstacles and input for these activities, conclusions The implementation of activities related to basic basketball techniques gets enthusiasm and can be highly motivated by the players.